Exosomes Derived From CTF1-Modified Bone Marrow Stem Cells Promote Endometrial Regeneration and Restore Fertility - Zhu, Qianqian; Tang, Shengluan; Zhu, Yanwen; Chen, Di; Huang, Jialyu; Lin, Jiaying (Frontiers in Bioengineering and Biotechnology, 2022)
Background: Thin endometrial tissue is a leading cause of embryo transfer failure, potentially contributing to sustained infertility and associated adverse outcomes. The application of exosomes derived from autologous or allogeneic bone marrow-derived stem cells (BMSCs) has been used to promote uterine repair following injury, and there is also prior evidence that stem cell transplantation can bolster fertility. Genetic modifications represent a primary approach to enhancing exosomal therapy strategies. The present study thus explored the effects of Cardiotrophin-1 (CTF1)-modified BMSCs-exo on fertility-related outcomes. Methods: An adenoviral vector was used to generate CTF1-overexpressing BMSCs (C-BMSCs), after which exosomes were isolated from control BMSCs (BMSC-exos) and C-BMSCs (C-BMSC-exos). The angiogenic effects of C-BMSC-exo treatment were assessed through analyses of endothelial cell proliferation and tube formation. Model rats exhibiting endometrial thinning were administered C-BMSCs-exo, after which the effects of such treatment were assessed through H&E staining, Masson’s trichrome staining, and immunofluorescence analyses. The mechanistic basis for the proangiogenic effects of CTF1 as a driver of endometrial regeneration was additionally explored. Results: C-BMSC-exo treatment of HUVECs was associated with enhanced neovascularization, as evidenced by improved in vitro proliferation, migration, and tube formation. Importantly, such treatment was also linked to tissue regeneration, neovascularization, and the suppression of localized tissue fibrosis in vivo. Regenerated endometrial tissue exhibited higher embryo receptivity and was associated with higher birth rates in treated rats. The upregulation of the JAK/PI3K/ mTOR/STAT3 signaling pathways in C-BMSC-exo-treated rats may underscore the mechanistic basis whereby CTF1 can positively impact endometrial angiogenesis and regeneration. Conclusion: Our data suggest that exosomes produced by CTF1-modified BMSCs can more effectively promote the regeneration of endometrial and myometrial tissues, driving neovascularization in a manner that improves endometrial receptivity in a rat model system, highlighting the therapeutic promise of this approach for patients diagnosed with endometrial thinning.